ESTIMASI PENGUKURAN PERANGKAT LUNAK MENGGUNAKAN METODE MATRIK FUNCTION POINT ANALYSIS – STUDI KASUS APLIKASI AKADEMIK SISWA BERBASIS WEBSITE (Jurnal Sistem Informasi dan Sains Teknologi, 2022)
Function Point (FP) is a measurement method as well as a unit of measure from a software. FP can measure software by quantifying (number of units in numbers) functionality in software that is already provided to users based on logic. The FP matrix is calculated from 5 components which include the number of user inputs (external input-EI), the number of outputs to the user (external inquiry - EQ), the number of user inquiries (external inquiry - EQ), the number of internal files used (internal logical file - EQ). ILF), and the number of external interfaces (external files – EIF). This case study aims to study carefully how to calculate FP which produces the final result in the form of cost estimation in software. The existing software is the Website-Based Student Academic Application (AASBW). The technical files available from this software are source code and running application. This FP measurement will be carried out from a software point of view, namely measuring the finished application. From the observation, it is found that the FP for AASBW = 152.90 and the estimated cost to market this application is Rp. 7,645.00, the estimated production time is 29 days, and the estimated cost of managing this application is Rp. 3,850,000, so the results of the three estimation factors are used by the authors as analysis material for Website-Based Student Academic Applications using the Function Point Analysis method.